1989
DOI: 10.1212/wnl.39.7.969
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficacy of intravenous methylprednisolone and ACTH in the treatment of acute relapse in MS

Abstract: To compare the efficacy of high-dose intravenous methylprednisolone with intramuscular ACTH in the treatment of acute relapse in multiple sclerosis, we undertook a double-blind, randomized, controlled study involving 61 patients. There was a marked improvement in both groups in the course of the study, but no difference between them in either the rate of recovery or the final outcome. High-dose IV methylprednisolone is a safe alternative to ACTH in the management of acute relapse in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 0 publications
0
84
0
Order By: Relevance
“…Additionally, daily administration of 500-1000 mg of MP increases serum steroid peak levels 5-10 times more compared with ACTH administration (54). Despite these, positive effects equivalent to MP have been reported with ACTH use in relapse treatment (59,60,61). This effect is attributed to the direct anti-inflammatory and immunomodulatory effects of ACTH through melanocortin receptors.…”
Section: Adrenocorticotropic Hormone and Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, daily administration of 500-1000 mg of MP increases serum steroid peak levels 5-10 times more compared with ACTH administration (54). Despite these, positive effects equivalent to MP have been reported with ACTH use in relapse treatment (59,60,61). This effect is attributed to the direct anti-inflammatory and immunomodulatory effects of ACTH through melanocortin receptors.…”
Section: Adrenocorticotropic Hormone and Steroidsmentioning
confidence: 99%
“…This effect is attributed to the direct anti-inflammatory and immunomodulatory effects of ACTH through melanocortin receptors. ACTH is showed to be effective in opsoclonus-myoclonus and infantile spasms via the melanocortin receptors whereas synthetic steroids are found to be ineffective in these conditions (62,63,64).…”
Section: Adrenocorticotropic Hormone and Steroidsmentioning
confidence: 99%
“…Of four trials that examined short-term treatment of patients with MS with an ACTH analogue compared with either placebo [Rose et al 1970] or IV MP [Abbruzzese et al 1983;Barnes et al 1985;Thompson et al 1989], few provided data pertinent to mood changes. A large study of 197 MS patients (n = 103, ACTH; n = 94, placebo) reported some evidence, albeit limited, of improvement in mood, but without further details about the types of mood changes [Rose et al 1970].…”
Section: Discussionmentioning
confidence: 99%
“…One study specified that of the three patients on MP and two on ACTH who failed to complete the study, one patient on ACTH 'became agitated and paranoid' on day 13 of treatment and was withdrawn from the study, though no other details were provided [Thompson et al 1989]. Finally, two of the studies of patients receiving either ACTH or MP did not provide information regarding mood changes in either group [Abbruzzese et al 1983;Barnes et al 1985].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia, hypertension, moon face, and hirsutism were less frequently reported [2,3,[18][19][20][21][22][23][24][25].…”
Section: Adverse Events During Steroid and Acth Therapymentioning
confidence: 96%